CREATIVITY IN STUDENTS THROUGH PHYSICAL EXPERIMENTS FORMATION OF THINKING SKILLS - Niyazimbetova, N.; Kamalov, A.B. (SCIENCE and SOCIETY, 2026)
This article examines the role of physical experiments in developing students’ creative thinking and problem-solving skills. The author emphasizes that experimental activities in physics lessons transform students from passive recipients of knowledge into active participants of scientific inquiry. The process of conducting experiments encourages students to observe, analyze, hypothesize, and draw conclusions independently. The article discusses the pedagogical importance of problem-based learning in physics education, showing how simple experiments can stimulate analytical and innovative thinking. Examples of effective classroom practices and modern digital tools used to organize experiments are provided.